Prove that 1+1=2.
Answers
Answered by
0
Hey,
Mate Here's the solution....
The proof starts from the Peano Postulates,
which define the natural numbers N. N is the
smallest set satisfying these postulates: P1. 1 is
in N. P2.
If x is in N, then its "successor" x' is in N. P3.
There is no x such that x' = 1. P4.
If x isn't 1, then there is a y in N such that y' = x. P5.
If S is a subset of N, 1 is in S, and the implication (x in S => x' in S) holds, then S = N.
Then you have to define addition recursively:
Definition : Let a and b be in N. If b = 1, then
define a + b = a' (using P1 and P2). If b isn't 1,
then let c' = b, with c in N (using P4), and define
a + b = (a + c)'. Then you have to define 2: Def:
2 = 1' 2 is in N by P1, P2, and the definition of 2.
Theorem:. 1 + 1 = 2 Proof: Use the first part of
the definition of + with a = b = 1. Then 1 + 1 = 1' =
2 Q.E.D. Note: There is an alternate
formulation of the Peano Postulates which
replaces 1 with 0 in P1, P3, P4, and P5. Then
you have to change the definition of addition
to this: Def: Let a and b be in N. If b = 0, then
define a + b = a. If b isn't 0, then let c' = b, with c
in N, and define a + b = (a + c)'. You also have to
define 1 = 0', and 2 = 1'. Then the proof of the
Theorem above is a little different: Proof: Use
the second part of the definition of + first: 1 + 1 =
(1 + 0)' Now use the first part of the definition of
+ on the sum in parentheses: 1 + 1 = (1)' = 1' = 2
Or..
Note that while 1 + 1 = 2 can be false if you use
different axioms, 1 + 1 = 2 is not itself an axiom.
So using the Peano Axioms (which are usually
implied unless otherwise stated), 1 + 1 = 2 can
only be true since it necessarily follows from
the axioms.
Mate Here's the solution....
The proof starts from the Peano Postulates,
which define the natural numbers N. N is the
smallest set satisfying these postulates: P1. 1 is
in N. P2.
If x is in N, then its "successor" x' is in N. P3.
There is no x such that x' = 1. P4.
If x isn't 1, then there is a y in N such that y' = x. P5.
If S is a subset of N, 1 is in S, and the implication (x in S => x' in S) holds, then S = N.
Then you have to define addition recursively:
Definition : Let a and b be in N. If b = 1, then
define a + b = a' (using P1 and P2). If b isn't 1,
then let c' = b, with c in N (using P4), and define
a + b = (a + c)'. Then you have to define 2: Def:
2 = 1' 2 is in N by P1, P2, and the definition of 2.
Theorem:. 1 + 1 = 2 Proof: Use the first part of
the definition of + with a = b = 1. Then 1 + 1 = 1' =
2 Q.E.D. Note: There is an alternate
formulation of the Peano Postulates which
replaces 1 with 0 in P1, P3, P4, and P5. Then
you have to change the definition of addition
to this: Def: Let a and b be in N. If b = 0, then
define a + b = a. If b isn't 0, then let c' = b, with c
in N, and define a + b = (a + c)'. You also have to
define 1 = 0', and 2 = 1'. Then the proof of the
Theorem above is a little different: Proof: Use
the second part of the definition of + first: 1 + 1 =
(1 + 0)' Now use the first part of the definition of
+ on the sum in parentheses: 1 + 1 = (1)' = 1' = 2
Or..
Note that while 1 + 1 = 2 can be false if you use
different axioms, 1 + 1 = 2 is not itself an axiom.
So using the Peano Axioms (which are usually
implied unless otherwise stated), 1 + 1 = 2 can
only be true since it necessarily follows from
the axioms.
Answered by
1
Proved☺️☺️☺️☺️☺️☺️☺️☺️☺️☺️☺️☺️☺️☺️☺️
Attachments:
Similar questions